Multi-agent-based modelling and simulation of high-speed train. (September 2020) - Kou, Li; Fan, Wenhui; Song, Shuang
Highlights: Chinese high-speed train has developed rapidly and gained worldwide recognition. Traditional simulation methods are not suitable for the emergence of complex systems. A multi-agent-based modelling and simulation technology can help to verify the design. The multi-agent-based method is more intelligent, flexible and time-saving. Abstract: In recent years, the Chinese high-speed train (HST) has achieved leapfrog development with independent innovation by introducing and incorporating new technologies. Modelling and simulation are the most effective and economical methods for research on the HST. However, the traditional methods are not suitable for the HST's large-scale systems, which contain numerous and complex structures, interactions, and emergence effects. In this paper, we propose a multi-agent-based modelling and simulation (MABMS) technology that can simulate the relationship between the individual behaviour and overall performance of the HST's components. The results provide the basis for analysing and studying the micro and macro level of the system. Meanwhile, we develop a new MABMS platform to perform additional experiments. Our simulation results indicate that this method is practicable and can play an important role in promoting the development of the HST. Graphical abstract: We propose a multi-agent-based modelling and simulation (MABMS) technology that can simulate the relationship between the individual behaviour and overall performance of the Chinese high-speed train's components. Image, graphical abstract